PEMBERIAN PUPUK KANDANG DAN UREA PADA BIBIT TANAMAN MAHONI (Switenia macrophylla King) - Azwin, Azwin (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
This study aimed to get a dose of manure and urea appropriate, as well as a good combination on the growth of seedling mahoni (S. macrophylla King). Research conducted an experiment using a completely randomized design (CRD) 2 factors, factors chicken manure (k) consists of four levels i.e. k0 (without manure), k1 (manure, 200 g / seeds), k2 (manure, 400 g / seed) and k3 (manure, 600 g / seed) and factor Urea (n) consists of four levels i.e. n0 (without urea), n1 (Urea 2.5 g / seeds), n2 (Urea 5 g / seed) and n3 (Urea 7.5 g / seeds), each replicated three times. Results of analysis of variance on a test level of 0.05 indicates that Manure significantly affected parameters plant height and number of lateral roots, while the stem diameter, number of leaves and length of main root effect is not real, the best treatment contained in k3 (manure 600 g / seed). Further provision of urea no real effect on all parameters was observed, while the combination of manure and urea real effect only on the parameters of the main root length and number of lateral roots is the best dose at 600 g / plant manure and 7.5 g / seedling urea. In parameter plant height, stem diameter and number of leaves no real effect.